Faktor Karakteristik dalam Kejadian Kekambuhan pada Pasien Skizofrenia - Putri, Triyana Harlia; Agustia, Yuni (Poltekkes Kemenkes Tanjung Karang, 2022)
Characteristics are factors that contribute to the recurrence factor, this can have an impact on decreasing the quality of life for both patients and families. This study aims to determine the characteristic factors that influence recurrence in schizophrenic patients. The method used in this study is a cross-sectional approach with a sampling technique using the purposive sampling method, the number of samples obtained in 81 patients. The research instrument used a sociodemographic questionnaire and the frequency of recurrence. Bivariate analysis using Fisher's test. The results indicate that the respondents are in late adulthood 55 (45,5%), with most of them being female 42 (51,9%), with the last education being SMA/SMK 42 (51,9%) and a small portion not working/housewife 32 (39,5%). The frequency of recurrence was in the low category 47 (58%). There was a correlation between age characteristics and relapse of schizophrenia patients (p-value<0,05), but statistically, no significant correlation was found on the characteristics of sex, education, and occupation. Patient characteristics are part of the factors that cause recurrence, however, adherence to medication and good family support can minimize the incidence of recurrence and improve quality of life.